2021
DOI: 10.3390/ani11010180
|View full text |Cite
|
Sign up to set email alerts
|

Free and Microencapsulated Essential Oils Incubated In Vitro: Ruminal Stability and Fermentation Parameters

Abstract: Essential oils (EOs) are generally considered as an alternative to antibiotics because of their antimicrobial properties. Despite their vast variety, their volatile nature poses hindrance on their use in animal feeds, which demands a high degree of stability. This study aimed at testing the susceptibility of three EOs (mixtures of EOs based on cinnamaldehyde, named Olistat-Cyn, Olistat-G, and Olistat-P) in two forms (free: fEOs; and microencapsulated: mEOs) to in vitro ruminal degradation using the Ankom Daisy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
1
12
1
1
Order By: Relevance
“…Negligible changes in pH due to GEO (Mateos et al 2013), REO (Castillejos et al 2008), and EEO (Cobellis et al 2016) have previously been reported. Decreases of pH were previously observed for CEO in vivo (Chaves et al 2008) and in vitro (Amin et al 2021). However, decreases are often related to VFA increases, not observed in the present study.…”
Section: Fermentation Parameterssupporting
confidence: 47%
“…Negligible changes in pH due to GEO (Mateos et al 2013), REO (Castillejos et al 2008), and EEO (Cobellis et al 2016) have previously been reported. Decreases of pH were previously observed for CEO in vivo (Chaves et al 2008) and in vitro (Amin et al 2021). However, decreases are often related to VFA increases, not observed in the present study.…”
Section: Fermentation Parameterssupporting
confidence: 47%
“…Essential oils (EOs) have been known to have varying chemical structures and bioactive compounds as they are extracted from different plants [ 1 ]. Essential oils are also known for their antiprotozoal and antimicrobial properties [ 2 , 3 ]. Due to their broad range of antimicrobial activities, EOs are commonly regarded as potential antibiotic replacements [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of EOs in ruminant diets has been reported to have significant influence in ruminant digestion and fermentation, as well as microbial populations and methanogenesis [ 5 , 6 , 7 , 8 ]. The use of EO blends (EOBs) over single EOs has been reported to be more advantageous [ 3 ]. Friedman et al [ 9 ] reported that by combining cinnamaldehyde with eugenol, cinnamaldehyde can be preserved from heat-induced degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the highly volatile nature of EOs, they are usually microencapsulated to protect from digestion in the upper digestive tract and thus maintain their efficacy in the lower bowel 22‐24 . The concept for EO microencapsulation is to provide a physical barrier for bioactive compounds from the environment and ensure a slow and progressive intestinal release 25 .…”
Section: Discussionmentioning
confidence: 99%